Caesarean sections before and during the COVID-19 pandemic in western Sydney, Australia - Lieu Thi Thuy Trinh; Helen M. Achat; Andrew Pesce (Taylor & Francis Group, 2023)
Background To determine the changes in emergency and elective caesarean section (CS) rates since the COVID-19 pandemic, identify the groups most affected, and examine changes in the factors associated with CS rates, and reasons for CS. Methods We conducted a retrospective cohort study using routinely collected data of 22,346 births from before the pandemic (January 2018-February 2020) and 18,597 births during the pandemic (March 2020-December 2021). Data were analysed using multinominal logistic regression. Results The CS rate increased by 4.1% (from 30.1% to 34.2%), reflecting increases of 2.3% in emergency CS (from 11.5% to 13.8%) and 1.7% in elective CS (from 18.7% to 20.4%). Large groups with notable increases were women who were nulliparous (7.2% increase), from South Asia (6.0%), obese (5.2%) and giving birth at a small hospital (6.1%). Compared to pre-pandemic, the relative risk of an emergency CS versus a vaginal delivery increased 1.36 times (adjusted relative risk ratio (aRRR) = 1.36; 95% CI = 1.27, 1.45) and the risk of having an elective CS increased 1.11 times (aRRR = 1.11; 95% CI = 1.04, 1.20). Factors associated with both emergency and elective CS were age, region of birth, reproductive history, body mass index, hypertension, diabetes, mode of antenatal care and hospital. Socio-Economic Indexes for Areas and antenatal care were only associated with elective CS. Baby gender was only associated with emergency CS. Preterm gestation at delivery was associated with reduced emergency but increased elective CS. Foetal compromise was the most common indication for emergency CS (43.2%) and increased the most (8.0%). Previous CS was the most common indication for elective CS (61.5%) and reduced the most (1.9%). Conclusions Both emergency and elective CS rates increased significantly during the pandemic, with the former increasing at a higher rate. The persistent upward trend of CS rates, exacerbated by increasing proportions of nulliparous women undergoing CSs, is concerning.